DC motor control using a four-quadrant chopper based on artificial neural networks - Rahmad, Rahmad Rizki; Hendra, Ayu; Yuhendri, Muldi (Department of Electrical Engineering Universitas Negeri Padang, 2024)
DC motors are widely used as drives in various industrial applications. To ensure optimal performance, precise control of DC motors is essential, including managing rotation direction, speed, braking, and starting current. This paper presents a speed control system for a DC motor using a 4-quadrant DC chopper with a neural network as the control core. The system is designed and implemented on a 12V DC motor and tested under varying speed conditions. Motor speed is adjusted in MATLAB Simulink according to operational requirements. The results confirm that the proposed DC motor speed control system, utilizing a four-quadrant chopper, functions effectively, providing accurate speed control through MATLAB Simulink.